‘It made me think a little different’ a qualitative study of young adult cancer survivors’ experiences of cognitive therapy in cancer rehabilitation. - Hauken, May Aasebø (International Journal of Psychosocial Rehabilitation, 2016)
Young adult cancer survivors (YACS) have increased risk for psychosocial late-effects. Cognitive therapy (CT) aims to enhance coping in survivorship, but research of CT interventions and how YACS experience these lacks. This study’s aim was to explore YACS’ experiences of CT in a rehabilitation program. A phe- nomenological-hermeneutical design was used, including semi-structured interviews of 17 YACS who com- pleted a rehabilitation program. Two main themes and three corresponding subthemes emerged: The first theme, «CT as a tool», was elabor - ated by the subthemes «education and practicing», «follow-up» and «internalization». The second theme, «the perceived usefulness of CT» was clarified by the three subthemes «changed thought patterns», «insight and ac- ceptance» and «handling a new life-situation».The participants experienced CT as a useful tool in their rehabilitation process that changed their thought pat - terns and helped them getting insight and acceptance as an important basis to handle their new life-situation.